2014
DOI: 10.1186/s12905-014-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV risks vary according to type of sex work in a cross-sectional survey from Nagaland, India

Abstract: BackgroundHuman immunodeficiency virus (HIV) infection is a significant problem among female sex workers (FSWs) in Nagaland, India. Place of solicitation and sex vary considerably in this context. The aim of this study was to investigate the relationship between categories of sex work and HIV risks.MethodsIn 2009 a survey was undertaken among 417 FSWs in Dimapur, Nagaland using an interviewer-administered questionnaire and blood and urine samples. Using this data, we constructed a typology of sex work by combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…[39][40][41][42][43][44][45][46] The study finding linking client solicitation in rented rooms to increased HIV risk is consistent to a study conducted in Nagaland, which reported that low levels of condom use by such FSWs, who may rely on lodge managers as client intermediaries, could be a reason for such high prevalence in this typology group. 23 The significant association of HIV positivity with mobile phone use in the study points towards need to integrate this aspect of sex work into HIV/AIDS interventions for FSWs. [47][48][49] Studies conducted in South India found that while the invisibility offered by mobile phone use to FSWs, through the establishment of a direct communication with their clients and reduction in their reliance on traditional sex work intermediaries (pimps and brothel managers), benefits them, it also prevents health and social services from reaching them.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[39][40][41][42][43][44][45][46] The study finding linking client solicitation in rented rooms to increased HIV risk is consistent to a study conducted in Nagaland, which reported that low levels of condom use by such FSWs, who may rely on lodge managers as client intermediaries, could be a reason for such high prevalence in this typology group. 23 The significant association of HIV positivity with mobile phone use in the study points towards need to integrate this aspect of sex work into HIV/AIDS interventions for FSWs. [47][48][49] Studies conducted in South India found that while the invisibility offered by mobile phone use to FSWs, through the establishment of a direct communication with their clients and reduction in their reliance on traditional sex work intermediaries (pimps and brothel managers), benefits them, it also prevents health and social services from reaching them.…”
Section: Discussionmentioning
confidence: 91%
“…The study finding linking client solicitation in rented rooms to increased HIV risk is consistent to a study conducted in Nagaland, which reported that low levels of condom use by such FSWs, who may rely on lodge managers as client intermediaries, could be a reason for such high prevalence in this typology group. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HIV and STIs varies widely among sex workers depending on where they work, such as in the street, at home or in a commercial establishment such as a bar and massage parlor. 46,47 The 2011 surveillance survey in Kathmandu valley found that the HIV prevalence was four times higher among FSW who worked on the street as compared to establishment-based sex workers. 42 Reducing police harassment of sex workers and understanding changes in the typical place of solicitation over time are thus also vital for adapting HIV prevention efforts to the needs of sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…Para essa elevada prevalência destacam-se os principais fatores: multiplicidade de parcerias sexuais, estado civil solteira ou separada, baixa escolaridade, capacidade reduzida para negociar práticas sexuais segura, ser trabalhadora sexual migrante, o uso de drogas estimulantes (cocaína, carck, metanfetamina) e de álcool, o compartilhamento de drogas injetáveis, vítimas de violência física (9,15) . MPS que possuem clientes constantes e regulares apresentaram sorologia negativa para HIV/IST (12) .…”
Section: Medidas Interventivasunclassified